2009
DOI: 10.1128/jcm.01099-09
|View full text |Cite
|
Sign up to set email alerts
|

Large Dissemination of VIM-2-Metallo-β-Lactamase-Producing Pseudomonas aeruginosa Strains Causing Health Care-Associated Community-Onset Infections

Abstract: a series of 45 outpatients presented with community-onset urinary tract infections due to carbapenem-resistant Pseudomonas aeruginosa isolates. Forty of them had a history of previous hospitalization or exposure to healthcare facilities, while the remaining five had not been previously admitted to our healthcare facilities or elsewhere within the preceding 12 months. In 18 outpatients, the carbapenem-resistant organisms caused recurrent community-onset urinary tract infections, while in three outpatients the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 27 publications
1
20
1
5
Order By: Relevance
“…Supporting evidence for this hypothesis is that despite the presence of factors adverse to antimicrobial effectiveness, such as renal lithiasis and papillary transitional carcinoma of urinary bladder, all outpatients were treated successfully with antimicrobial regimens. In contrast, previous studies have shown that MBL-producing Pseudomonas aeruginosa and Klebsiella pneumoniae strains are frequently associated with recurrent community-onset infections (19,24).…”
Section: Discussionmentioning
confidence: 60%
“…Supporting evidence for this hypothesis is that despite the presence of factors adverse to antimicrobial effectiveness, such as renal lithiasis and papillary transitional carcinoma of urinary bladder, all outpatients were treated successfully with antimicrobial regimens. In contrast, previous studies have shown that MBL-producing Pseudomonas aeruginosa and Klebsiella pneumoniae strains are frequently associated with recurrent community-onset infections (19,24).…”
Section: Discussionmentioning
confidence: 60%
“…Based on the results, 31 P. aeruginosa and 3 A. baumannii isolates were found to carry MBL genes including blaIMP1 and blaVIM2 (19). In Greece during 3 years, large dissemination of P. aeruginosa producing blaVIM2 was studied (24).…”
Section: Discussionmentioning
confidence: 99%
“…The researchers reported that the major cause of (urinary tract) infections in nosocomial acquisition samples was P. aeruginosa producing MBL (24). In an Australian paper (25) published in 2010, dissemination and genetic variants of MBLs producing P. aeruginosa isolates recovered from four countries including Korea, India, Taiwan, and Philippines were examined.…”
Section: Discussionmentioning
confidence: 99%
“…Such integrons have the potential to dramatically enhance the fitness of the host bacterium in the health care setting (39,135,175). Integron-associated antibiotic resistance genes have been identified in several outbreaks of strains producing metallo-␤-lactamases (MBLs) (74,111,163,172,215). Like KPC ␤-lactamases, MBLs hydrolyze most ␤-lactam antibiotics, including carbapenems (31,134,223).…”
Section: Transposons Insertion Sequences and Integronsmentioning
confidence: 99%